2022
DOI: 10.1007/s11356-022-21589-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of per- and polyfluoroalkyl substances (PFAS) in waters from Central and South Florida

Abstract: Per-and poly uoroalkyl substances (PFAS) are notoriously persistent pollutants that are found ubiquitously present in aquatic environments. They pose a big threat to aquatic life and human health given the bioaccumulation feature and signi cant adverse health effects associated. In our previous study, PFAS were found in surface waters from Biscayne Bay and tap waters from the West coast of South Florida, at levels that arouse human health and ecological concerns. Considering that Florida supports millions popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…These plants served approximately 53% of the population and identified twelve specific PFAS analytes, including six C5-C10 perfluoroalkyl carboxylic acids (PFCAs), four C4-10 perfluoroalkyl sulfonic acids (PFSAs), and two fluorotelomer sulfonates (FTS) -namely, 6:2 and 8:2 FTS. In Florida, Li et al (2022) reported the ubiquitous presence of PFAS in both tap water (N = 10) and surface water samples (N = 38). The total concentrations in these samples reached as high as 169 ng L −1 , with notably elevated levels (> 60 ng L −1 ) observed in areas near sources such as military airbases, wastewater facilities, and airports, as well as in polluted rivers or coastal estuaries like Biscayne Bay.…”
Section: Introductionmentioning
confidence: 99%
“…These plants served approximately 53% of the population and identified twelve specific PFAS analytes, including six C5-C10 perfluoroalkyl carboxylic acids (PFCAs), four C4-10 perfluoroalkyl sulfonic acids (PFSAs), and two fluorotelomer sulfonates (FTS) -namely, 6:2 and 8:2 FTS. In Florida, Li et al (2022) reported the ubiquitous presence of PFAS in both tap water (N = 10) and surface water samples (N = 38). The total concentrations in these samples reached as high as 169 ng L −1 , with notably elevated levels (> 60 ng L −1 ) observed in areas near sources such as military airbases, wastewater facilities, and airports, as well as in polluted rivers or coastal estuaries like Biscayne Bay.…”
Section: Introductionmentioning
confidence: 99%